COMPARISON BETWEEN TESTICULAR PALPATION AND INDIRECT ELISA FOR THE DIAGNOSIS OF OVINE BRUCELLOSIS - Troncoso T., Ignacio (2014)
The diagnosis of ovine brucellosis in Chile is based on clinical examination of the testicles and confirmed with a serological test, being the complement fixation test, agar gel immunodiffusion test and the indirect ELISA the most used. The present study was carried out in the Municipality of San Ignacio, VIII Chilean region in 40 rams with the aim of comparing two diagnostic tools: testicular palpation and indirect ELISA for the antibody detection against Brucella ovis. The results showed 12 (30%) rams positive to testicular palpation and 5 rams (12.5%) positive to ELISA, where the level of agreement between the two diagnostic tests was poor (k=0.0714). Positive rams to brucellosis based on testicular palpation are not necessarily infected with B. ovis.